A study on the relationship between operational cash flow and the return of stockholders - Hassan Ghodrati; Hassan Abyak (Management Science Letters)
Performance measurement in managerial accounting is normally associated with cash flow and it is executed based on different figures such as testing information content abuse and accounting figures. However, increasing the information content in accrual components of earning and internal performance measurement provides additional informative insights. This paper studies the relationship between operating cash flows and earnings along with total shareholder returns. The study chooses the information of 54 firms from Tehran Stock Exchange. The results show that there were some meaningful relationship between the operating cash flow, profitability and the returns of all stakeholders. However, this happens by increasing profitability and cash flow of information asymmetry proportion to their correlation with the economic efficiency of shareholders’ returns.